2020
DOI: 10.1136/annrheumdis-2020-217256
|View full text |Cite
|
Sign up to set email alerts
|

Association of theRPA3-UMAD1locus with interstitial lung diseases complicated with rheumatoid arthritis in Japanese

Abstract: ObjectivesThe genetic background of rheumatoid arthritis–interstitial lung disease (RA-ILD) has been evaluated in Europeans, but little knowledge has been obtained in non-Europeans. This study aimed to elucidate genome-wide risk of RA-ILD in non-Europeans.MethodsWe performed an initial genome-wide association study (GWAS) of RA-ILD in the Japanese population. By conducting the meta-analysis of the three GWAS datasets of the RA cohorts and biobank of Japanese, our study included 358 RA-ILD cases and 4550 RA sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
0
22
3
2
Order By: Relevance
“…Meta-analysis of our data combined with the data from the previous report 4 was performed under the random effects model and did not reach the genome-wide significance threshold ( Supplemental Figure 1 ; P = .0996, OR 1.52, 95% CI 0.92-2.49; the weight of this study in the random effects model was 42.2%). The lack of heterogeneity was not confirmed between our data and the previously reported data on rs12702634 ( I 2 = 74.6%, τ 2 = 0.0980, H = 1.99, Q = 3.94, P = .0470); these data supported the analysis under the random effects model.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Meta-analysis of our data combined with the data from the previous report 4 was performed under the random effects model and did not reach the genome-wide significance threshold ( Supplemental Figure 1 ; P = .0996, OR 1.52, 95% CI 0.92-2.49; the weight of this study in the random effects model was 42.2%). The lack of heterogeneity was not confirmed between our data and the previously reported data on rs12702634 ( I 2 = 74.6%, τ 2 = 0.0980, H = 1.99, Q = 3.94, P = .0470); these data supported the analysis under the random effects model.…”
Section: Resultsmentioning
confidence: 76%
“…A recent genome-wide association study (GWAS) of ILD in RA in a Japanese population identified a significant association with a single nucleotide polymorphism (SNP), rs12702634, in the RPA3-UMAD1 gene. 4 An association of this SNP with ILD in Japanese RA patients was analyzed in the present study to replicate this association.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a Japanese GWAS, the SNV rs12702634 in the RPA3-UMAD1 gene proved to have a major association with the development of RA-ILD. This genetic polymorphism was mostly associated with the UIP pattern [ 37 , 38 , 39 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) have been conducted to determine the role of common variants on disease predisposition; a Japanese GWAS was performed for ILD in RA with the result that a significant association with SNV rs12702634 in the RPA3-UMAD1 gene was found. 76 Deleterious rare variants including loss of function variants and deleterious missense variants are causative in some diseases. 77 A role for rare variants in the genes responsible for IPF was reported in European RA patients with ILD.…”
Section: Genetic Biomarkers For Ra-ild or Aodildmentioning
confidence: 99%